WOMEN'S ECONOMIC CONTRIBUTION IN THE FAMILY: A CONTEXTUAL ANALYSIS OF SOCIAL HADITH - Didin Chonyta; Raadliyatush Shalihah (IZZI: Jurnal Ekonomi Islam, 2025)
Social and economic changes in the contemporary era have encouraged more and more Muslim women Muslim women to engage in family economic activities, either as the primary breadwinners or as contributors to household income. This study aims to understand women's economic contributions from the perspective of social hadith through a contextual approach. Hadiths related to work, breadwinning, and women's contributions are examined not only based on the strength of their chains of transmission and texts but also analyzed within the social context of their time. The method used is qualitative library research, involving the identification and analysis of relevant hadiths, as well as referencing the views of classical and contemporary scholars. The findings indicate that Islam provides legitimate space for women to contribute economically, provided they uphold ethical values, family responsibilities, and principles of social justice. Social hadiths serve as a crucial foundation for building an inclusive, fair, and contextual understanding of women’s economic roles within contemporary Muslim families.